Asymmetric Effects of Favorable and Unfavorable Information on Decision Making Under Ambiguity - Peysakhovich, Alexander; Karmarkar, Uma R. (Management Science, 2016)
Most daily decisions involve uncertainty about outcome probabilities arising from incomplete knowledge, i.e., ambiguity. We explore how the addition of partial information affects these types of choices using theoretical and empirical methods. Our experiments in both gain and loss domains demonstrate that when such information supports a favorable outcome, it strongly increases valuation of an ambiguous financial prospect. However, when information supports an unfavorable outcome, it has significantly less impact. We find that two mechanisms drive this asymmetry. First, unfavorable information decreases estimates of a good outcome occurring but also reduces aversive uncertainty. These factors act in opposition, minimizing the effects of unfavorable information. Second, when information can be subjectively interpreted, unfavorable information is less likely to be integrated into evaluations. Our findings reveal mechanisms not captured by traditional models of decision making under uncertainty and highlight the importance of increasing the salience of unfavorable information in uncertain contexts to promote unbiased decision making. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2015.2233 . This paper was accepted by Teck-Hua Ho, behavioral economics.